PENERAPAN SISTEM INFORMASI GEOGRAFI PENCARIAN BENGKEL TERDEKAT MENGGUNAKAN GPS SMARPHONE DI DAERAH ISTIMEWA YOGYAKARTA - Sudirman -; Erna Kumlasari N; Erfanty Fatkhiyah (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
Tourists who were vacationing in Yogyakarta and not too familiar with the city of Yogyakarta, usually find it difficult to search for public services, particularly in this case Vehicle Repairs both two-wheeled vehicles or four-wheeled vehicle repair shop. It is not only a waste of time but wasting a lot of energy and materials as well as to take the journey. This research aims to create mobile based applications to help people, especially tourists visiting Yogyakarta to find the location of the bike shop and car in Yogyakarta. Apart from it can build an information service that collects data for the garage and the services provided and can help the mechanic to be able to find the location of customers who are in need of repair vehicle.The results of this research are mobile based applications and web based applications. Applications built with client server model, which is using the Apache web server MySQL database system as a data storage center. The mobile application is used for the customer and the workshop. While web application for administrators. The mobile application has several features, among others, the workshop registration, customer registration, location search workshop and search the customer's location. While the web application features the administrator to manage all transactions and completeness.